The Gig Economy and its Implications for Human Resource Management in Jambi: A Preliminary Investigation - Abu Bakar; Ariyanto M; Zulkifli; Darmawanto; Hamirul (Enigma Institute, 2024)
The gig economy, characterized by temporary and flexible work arrangements, is rapidly expanding globally. However, its implications for human resource management (HRM) in developing regions like Jambi, Indonesia, remain largely unexplored. This study aims to provide a preliminary investigation into the gig economy's impact on HRM practices in Jambi. A mixed-methods approach was employed, involving a survey of 150 gig workers and 50 traditional employees in Jambi, along with in-depth interviews with 10 HRM professionals from various industries. The survey data was analyzed using descriptive statistics and comparative analysis, while the interview data was analyzed thematically. The study found that gig workers in Jambi face challenges related to job insecurity, lack of benefits, and social isolation. HRM professionals reported difficulties in recruiting, managing, and retaining gig workers due to the lack of formal employment contracts and the need for flexible work arrangements. The findings also suggest that the gig economy is creating new opportunities for HRM practices, such as the use of technology for talent acquisition and performance management. In conclusion, gig economy is transforming the nature of work in Jambi, posing challenges and opportunities for HRM. This study highlights the need for HRM professionals to adapt their practices to the changing landscape of work. Further research is needed to explore the long-term implications of the gig economy for HRM in Jambi and other developing regions.